Analisa Status Tentara Bayaran dalam Konflik Bersenjata dan Dampaknya bagi Perdamaian Dunia Ditinjau dari Perspektif Hukum Humaniter Internasional - Fahrurrozi, Achmad; Valda, Dennise Ignacia Evania (Proceedings Series on Social Sciences & Humanities, 2024)
This article examines the status of mercenaries in international armed conflicts. Mercenaries are not a new concept in International Law and International Humanitarian Law, both in terms of theory and practice. In Additional Protocol I Article 47 of the 1977 Geneva Conventions, mercenaries are specifically defined with certain criteria. This definition applies to armed conflicts, both domestic and international. In addition, this definition is also relevant in situations of mass violence aimed at overthrowing a government or threatening a country's constitution, law, economy, financial order or valuable natural resources. Although mercenaries are legally recognized in Article 47 of the 1977 Additional Protocol, they do not have rights as combatants and prisoners of war, this places them in a gray zone status, so they may violate existing international legal instruments and have a negative impact on stability and security.